ANALISIS KORELASI DAN REGRESI ANTARA TAHUN BERDIRI DENGAN NILAI DEVIASI ARAH KIBLAT MASJID AGUNG SE-JAWA TIMUR - Agus, Agus Solikin; Damanhuri, Adi (Universitas Muhammadiyah Surabaya, 2024)
This research aims to determine the correlation and regression between the year the Majid Agung was founded in East Java and the deviation value in the direction of the Qibla. The research method used is quantitative with simple correlation analysis which is based on guidelines for interpreting the correlation between the independent variable and the dependent variable. This research also uses linear regression. The deviation value of the Qibla direction of the Great Mosque is the dependent variable, and the year of its establishment is the independent variable. Correlation and linear regression calculations using Microsoft Excel. Based on the research that has been carried out, it was found that there was a very low correlation between the year it was founded and the deviation value in the Qibla direction of the Great Mosque building, namely 0.016, with the regression equation y=0.0009x+6.7736 and the variable the year the Great Mosque was founded only affected the Qibla direction deviation value by 0.03%,. based on the classification of great mosques into 4 (four) categories of centuries of existence, it shows that category 1, category 2, and category 3 have a negative correlation and each has a very low correlation, namely -0.128026886 for categories 1 and -0, 048713168 for category 2. Meanwhile, category 3 has a moderate correlation, namely -0.419826395, with the coefficient of determination of the year of establishment on the Qibla direction deviation value of 17.64% while 82.46% comes from other variables. Category 4 has a positive correlation and includes low correlation with a correlation coefficient of 0.24422172 and a coefficient of determination for the year of establishment with a Qibla direction deviation value of 5.96% while 94.04% comes from other variables